Analysis of Assertive Illocutionary Acts in the Movie Titled Up - Putu Agus Kurnia Ary Pratama (Institut Agama Islam Negeri Palopo, 2025)
This research analyzes assertive illocutionary acts contained in the dialogue of the animated film